Gabapentinoids: The rise of a new misuse epidemics?. (November 2021) - Hofmann, Michel; Besson, Marie
Highlights: Pregabaline and gabapentine abuse is on the rise. The risk factors for gabapentinoid abuse are the same as for opiates. Their lethality is linked to the increase they cause in opiate-related mortality. Prescribing gabapentinoids should take into account the risk of abuse. The management of chronic pain shouldn't rely on medication alone. Abstract: Gabapentinoids and opioids have in common that they are used in medicine in the treatment of pain, and by addicts in recreational use. In recent years, in the context of the "opioid epidemics", gabapentinoids, which had a reputation for low risk of abuse, have been increasingly prescribed. This was accompanied by increasingly frequent abuses, the patients most at risk being those suffering from opiate addiction. However, gabapentinoids increase the risks associated with opioids or other sedatives, due to a synergy of central depressant effects. This leads to reconsider the framework of their prescription and the management of chronic pain.